Commitment, Competence, and Partnership Model for Culinary MSMe Entrepreneurs In Bogor City - Muizu, Wa Ode Zusnita; Kaltum, Umi; Prasetyo, Andreas Recki; Triski, Dara Sagita (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research Aim: This study aims to analyze the commitment and competency levels of culinary MSMEs in Bogor City amidst intense competition and rising operational costs. Approach : Using a descriptive analysis method, the research was conducted for forty-five days from August to October 2023 on culinary MSMEs in Bogor City, applying simple random sampling to collect primary data. Research Findings : The results show that both commitment and competency levels of culinary MSME actors are very high. The main strength of these MSMEs lies in their growth orientation through horizontal integration strategies, which enhance business sustainability and competitiveness. Theoretical Contribution/Originality : This study contributes to MSME development theory by emphasizing the role of commitment and competency as key determinants of success. It also introduces a positioning map for culinary MSMEs in Bogor City, highlighting their comparative advantages. Practitioner/Policy Implication: The findings suggest that policymakers and business practitioners should strengthen partnership programs and collaborative initiatives to optimize the high commitment and competency levels of MSMEs, thereby improving competitiveness and resilience. Research Limitation : This research focuses solely on culinary MSMEs in Bogor City within a specific period (August–October 2023), limiting the generalizability to other regions or sectors.